The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1530/rep-15-0496
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2α promotes angiogenesis and embryo–maternal interactions during implantation

Abstract: Implantation in humans and other mammals is a critical period during which high embryonic mortality rates occur. Prostaglandins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 66 publications
1
52
0
3
Order By: Relevance
“…The effects of E2 administered directly into the uterine lumen was studied using in vivo models [88]. Prepubertal crossbred gilts of similar age (6 months) and genetic background after the second natural estrous cycle were treated hormonally with 750 I.U.…”
Section: Effect Of E2 On Porcine Endometrium In Vivomentioning
confidence: 99%
“…The effects of E2 administered directly into the uterine lumen was studied using in vivo models [88]. Prepubertal crossbred gilts of similar age (6 months) and genetic background after the second natural estrous cycle were treated hormonally with 750 I.U.…”
Section: Effect Of E2 On Porcine Endometrium In Vivomentioning
confidence: 99%
“…However, it should not be regarded as undesirable factor in pregnancy because elevated amounts of PGF2α in the uterine lumen and/or its increased endometrial synthesis occur not only in pigs (Zavy et al 1980, Waclawik et al 2006 but also in other mammals including rodents, cattle, dogs and humans (Kennedy et al 2007, Ulbrich et al 2009, Wang et al 2010, Vilella et al 2013, Kowalewski et al 2014. Moreover, a novel role for PGF2α in the porcine endometrium during the peri-implantation period has been recently reported by our group, indicating that PGF2α participates in pregnancy establishment by promoting angiogenesis and expression of genes involved in endometrial remodeling and embryomaternal communication (Kaczyński et al 2016).…”
Section: Introductionmentioning
confidence: 73%
“…PGE2 has been described as playing a luteoprotective/luteotrophic role (Waclawik et al 2008, Waclawik 2011 whereas PGF2α has been mainly perceived as a luteolytic factor in sheep, cattle and pigs, as well as in rats, rabbit and hamsters (reviewed in McCracken et al 1999). Thus, it could also have a detrimental effect in pregnancy development in mammals, including human, cattle, pigs and dogs (reviewed in Kaczyński et al 2016). However, it should not be regarded as undesirable factor in pregnancy because elevated amounts of PGF2α in the uterine lumen and/or its increased endometrial synthesis occur not only in pigs (Zavy et al 1980, Waclawik et al 2006 but also in other mammals including rodents, cattle, dogs and humans (Kennedy et al 2007, Ulbrich et al 2009, Wang et al 2010, Vilella et al 2013, Kowalewski et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, SGK1 contributes to early angiogenesis by inducing expression of Notch‐signaling genes (93). Although these findings have been conducted mainly on embryos and endothelial cell cultures, considering the highly conserved and ubiquitous expression of SGK1 , further studies in these areas might reveal a potential role for SGK1 in fertility and pregnancy maintenance from the perspective of vasculogenesis, which is a unique part of implantation (94). Of note, it has been suggested that SGK1 impairs human endometrial receptivity in diabetes (20).…”
Section: Discussionmentioning
confidence: 99%